Surface engineering of titanium alloy TiAl6V4 by multi-interstitial diffusion using plasma processing. Issue 1 (31st December 2022) - Drouet, Michel; Pichon, Luc; Vallet, Yves; Le Bourhis, Eric; Christiansen, Thomas L.
Abstract: Titanium alloy Ti6Al4V possesses a range of highly interesting properties such as excellent corrosion resistance, bio-compatibility and high specific stress but suffers from poor wear resistance. The present work addresses plasma assisted surface treatment using various combinations of nitriding and oxidizing treatments for improving the surface properties of this alloy. The response to the surface treatments is investigated by hardness depth profiling in correlation with the chemical and microstructural evolution. It highlights the advantages of combined nitriding and oxidizing treatments compared to single nitriding for improving surface mechanical properties of titanium alloys.